Prostate cancer in the Arab world: Bibliometric review and research priority recommendations. Issue 2 (3rd April 2022) - Ali, Adel Hajj; Awada, Hussein; Nassereldine, Hasan; Zeineddine, Mohammad; Sater, Zahy Abdul; El-Hajj, Albert; Mukherji, Deborah
ABSTRACT: Objective: To conduct a scoping review examining the status of prostate cancer research in Arab countries and systematically map publications across the cancer care pathway. Prostate cancer incidence has been rising in the Arab world and tackling its increasing burden will require evidence-based policies. Methods: We searched Medline, PubMed and Scopus for peer-reviewed publications related to both our research topic and countries of interest by using controlled vocabulary and keywords. Search results were limited for the period between 2000 and 2020, screened for duplicates, and then included in our study based on pre-specified eligibility criteria. We used a structured data extraction form to extract information related to the article, its methodology, its cancer care pathway, funding status, and authorship. Results: A total of 4142 publications were retrieved from our search, of which 874 articles remained after applying eligibility criteria. Trends show a steady increase in prostate cancer research in the Arab world. Most studies were focussed on diagnosis and treatment, whereas a lack in studies concerning screening and prevention, as well as epidemiological data, was evident. Most studies were not funded and had no female author. Country gross domestic product and population were positively correlated with its research output. The USA had the highest number of corresponding authors. The majority of Arab-based studies did not involve collaborations with other countries. Most research conducted was basic or clinical studies with a low level of evidence. Conclusion: Our present review identified significant gaps and limitations in prostate cancer research in Arab countries. Priority areas for research investment have also been highlighted as a first step towards context-specific health policies. Abbreviations: ASR: age-standardised rate; COVID-19: coronavirus disease 2019; GDP: gross domestic product; HDI: Human Development Index; KSA: Kingdom of Saudi Arabia; UAE: United Arab Emirates